Analysis of Offline Marketing Challenges in the Era of Digitalization among Micro, Small, and Medium Enterprises; A Case Study of Warung Bakso A Rohim - Ahmad Buchori Razak; Marliyah Marliyah; Sugianto Sugianto (Fakultas Syariah IAIN Langsa, 2026)
Ideally, Micro, Small, and Medium Enterprises (MSMEs) are expected to leverage marketing digitalization to expand market reach, enhance product visibility, and strengthen business competitiveness. In reality, however, many MSMEs continue to rely heavily on offline marketing strategies and encounter substantial barriers in adopting digital marketing practices effectively. This condition is evident in Warung Bakso A Rohim, a culinary MSME located in Medan City, which maintains conventional marketing practices amid the rapidly evolving digital marketing landscape. This study aims to analyze the challenges of offline marketing faced by MSMEs in the era of digitalization and to identify the factors influencing their marketing adaptation process. The research employs a field-based qualitative approach using a case study methodology, with data collected through in-depth interviews, direct observation, and documentation. The findings reveal that the persistence of offline marketing is driven by strong social relationships with local customers, limited digital literacy, constraints in human resources, and the absence of integrated online marketing within long-term business planning. These results indicate that MSME marketing transformation should be understood as an adaptive and gradual integration process between offline and digital strategies rather than a complete technological shift.